Design of Household Electricity Protection and Monitoring Automation With IoT ESP32 - Satria, Habib; Mual Gunawan Lubis, Mangara; Muthia Putri, Syarifah (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
existence of a household electrical protection and monitoring system to minimize danger. Therefore, a prototype design tool for household electricity protection and monitoring automation with IoT ESP 32 is developed. With the aim of carrying out voltage protection and electricity monitoring with a normal voltage of 220 VAC. designed to increase the existing protection system in the household, not to replace the function of the MCB. With a success rate of 99.6% voltage measurement, 97.5% current and 97.8% power measurement. Testing the tool using an inductive load in the form of a 45 watt 35, watt, 26 watt LED lamp and a resistive load in the form of a 400 watt iron set at the maximum hot point. below 210 VAC.